Síntese e avaliação da atividade leishmanicida de novos compostos 4-aminoquinolínicos - Barros, Daniele Costa Souza (2019)
Leishmaniasis, according to the World Health Organization, is among the seven major tropical diseases, endemic in 98 countries and is considered a public health problem that causes 20 to 40 thousand deaths annually. The control of the disease is a challenge faced by the competent authorities due to the diversity of agents, vectors and reservoir, besides the appearance of parasites resistant to much of the therapeutic arsenal used. Drug treatment, mainly focused on pentavalent antimonials, causes several side effects that end up decreasing therapeutic adherence and consequently increasing parasitic resistance. Compounds containing the quinoline nucleus have a wide variety of biological effects, including antimalarial and antileishmanial activity. In this context, the synthesis, characterization and evaluation of the leishmanicidal activity of four new 4-aminoquinoline compounds: D4, D5, D6 and D7, as well as the starting compounds D1 and D3, and the symmetrical D2 bisquinoline, were used. biological. The new compounds were obtained through two different methodologies, the first two (D4 and D5) via Sonogashira reaction and the other two (D6 and D7) via nucleophilic aromatic substitution reaction (SNAR). All were characterized by 1H and 13C (NMR) nuclear magnetic resonance spectroscopy, as well as Infrared Region (IR) Absorption Spectroscopy. The yield of the obtained products were moderate, being between 40 and 70%. The seven 4-aminoquinolinic compounds were evaluated for i) their toxicity in J774.A1 macrophages ii) their in vitro activity against L. amazonensis promastigotes iii) their in vitro activity against L. chagasi promastigotes. The results showed that in the evaluation of cytotoxicity compounds D1 and D5 had the lowest toxicity (LC50 87.8 ± 4.5 and 88.6 ± 11.6) among the compounds tested, in addition to D3 that showed no toxicity up to the maximum concentration (100 μM). In the evaluation of the leishmanicidal activity, monoquinolines D4 and D5 showed no significant activity until the maximum concentration used, although the starting compound D3 showed good activity against L. chagasi (LC50 10 μM ± 1,4). The dissimetric D6 and D7 bisquinolines showed activity against the promastigote forms of L. amazonensis and L. chagasi, however, the D6 was the best activity against both species (CI50 5.7 ± 1.8, 8.2 ± 0, 4). The other compounds were not active until the maximum concentration tested. In summary, the work showed that the formation of the bisquinolines favored the increase of the leishmanicidal activity in vitro when compared to the monoquinolines, at least in front of the analyzed species and in the concentrations tested.